Effectiveness of Ecotourism: A case of Chitwan National Park - Bhatt, Damodar Prasad; Dhakal, Tek Nath (Journal of Advanced Academic Research, 2018)
Ecotourism is the fast growing industry in the world. In Nepal also it is growing consistently since late 1980s.Various ecotourism programs have been initiated in different natural destinations in the country since then. But the research studies to find out the effectiveness of these programs have been rarely conducted. Very few studies have been conducted to know whether these programs are yielding desired results or not. This study aims to conduct one such research to find out the impact of a ecotourism program. The study is to be conducted in Chitwan National Park. The focus of the study is the buffer zone program of Chitwan National Park .Where the study aims to assess the impacts of community development activities of the buffer zone program. For that proposed conceptual frame work of the study is also presented below.